Female Labor Participation In Increasing Household Income (Case Study Section VI PT. Nusaina Agrocobi Manise) - Nur Ida Wati; Junianita F. Sopamena; Esther D. Leatemia (International Journal of Economics, Business and Innovation Research, 2023)
This research aims toknow the participation and factors that influence women's labor participation. The method of analysis using analysisdescriptive and logistic regression.The results of the study show that the participation of the female workforce is as casual daily workers. The results of the logistic regression analysis test show, togetherall independent variables affect the participation of female workers in increasing household income. This is because the Sig value > 0.05 = α so that hypothesis a is accepted.